Research on wind comfort regulation strategies for public spaces in aged residential communities of cold regions during windy spring seasons - Wen Xue; Xiaojun Guo; Xiaodan Chen; Yuanfeng Wang; Rui Chai; Yichao Wang; Yu Xia; Qianjun Cai (PLoS ONE, 2025)
In this study, the outdoor space of an aged residential community in Zhangjiakou, China, where strong winds frequently occur during the spring season, was investigated for environmental modifications. The study employed Rayman software to analyze the acceptable outdoor wind comfort range for residents, and utilized EDDY 3D simulation software to simulate and assess the current outdoor wind environment in the district. The analysis revealed that wind comfort was inadequate in several outdoor activity areas. The study suggests that the combination of landscape walls, enclosed spaces, and windbreak plants can effectively enhance wind environment conditions. The results indicate that: (1) The opening at the bottom of the wind-blocking wall can improve the static wind area at the corner, promote air circulation, and prevent pollutant accumulation. The larger the opening, the broader the influence of the wind shadow area and the greater the wind comfort area. (2) In cubic outdoor enclosed spaces, the degree of enclosure affects wind field conditions. Among these, the primary factor in enhancing the wind comfort area is the level and quantity of shelters perpendicular to the wind direction; the wind velocity variation in the wind shadow area is positively correlated with the degree of space enclosure. (3) Among the combinations of windbreak plants, the landscape configurations featuring equal height and gradient elevation arrangements. (4) After implementing the above three strategies to renovate the outdoor space of aged residential community, a computer simulation indicated that, under prevailing spring wind conditions, the wind-comfortable outdoor area increased from 40.26% to 79.84% demonstrate superior wind protection efficacy.